Organic compounds isolated from Juniperus brevifolia bark - Vieira, Amélia (2013)
In continuation of our study on the chemical characterization of endemic plants of the Azores archipelago, we have examined Juniperus brevifolia. Our interest in this plant was stimulated by the wide range of biological activities reported for other species of this genus and/or of their constituents. Previous work showed that leaves extracts, for instance dichloromethane extract and chloroform-soluble fraction of the acetone extract, showed high activity against HeLa and Hep-2 tumour cell lines. Chemical investigation of these extracts afforded more than thirty compounds, mainly abietane and pimarane derivatives, eight of them were new natural compounds and other exhibit interesting antitumor activity.These findings prompted us to study bark extracts.